THE STUDENT’S LEARNING STYLE AND THEIR WRITING SKILL AT SMK TIARA AKSARA - Eka Sari; Ikhfi Imaniah; Immtihan Hanim (Universitas Muhammadiyah Tangerang, 2020)
Writing is an activity that not only need physical act but also mental act. Students can put their statements, idea and opinion in composing writing. Moreover, students learn with visually, auditory and kinesthetic. Students with multi learning style usually better in learning and understand lessons, particularly in writing. Due to the statement, this study is aimed to find out the correlation between students’ learning style and their writing skill. This study use survey quantitative method and analyze the data by using statitisctical hypotheses. Based on the data analysis, it was found that student’s learning style was not normally distributed, whereas the data of writing test was normally distributed. Therefore, the researchers used non-parametric statistics to analyze the hypotheses. Kendall Tau calculation was used and obtained that Zcount ((0,35) < Ztable (1,96) with significant 0,05. Thus, H0 is accepted and Hi is rejected. It means that there is no correlation between students’ learning style and their writing skill. In this case, learning style were not dominat factors affected writing skill.